Dermatophytosis And Human Immunodeficiency Virus(HIV) Infection - Sentamilselvi G; Kamalam A; Ajithandas K; Janaki C (Wolters Kluwer Medknow Publications, 1998)
The incidence of Human Immunodeficiency Virus (HIV) antibody through Enzyme Linked Immunosorbant Assay (ELISA) technique was observed to be 2.5% among the 200 patients with dermatophytosis. The incidence was less (1%) in those with chronic disease compared to those with nonchronic disease (4%). The positivity seemed to be more in females screened. The clinical presentation of dermatophytosis in HIV positive patients was similar to that screen in general population. Trichophyton rubrum was the commonest isolate. Unusual widespread lesions and atypical lesions of nails like proximal subungual white onychomycosis were not encountered in the present series.